Analytical solution of Kompaneets equation - Karnaushenko, A.V. (Advances in Astronomy and Space Physics, 2012)
Analytical solution of Kompaneets equation, describing the movement of shock front from the strong point explosion in the medium with the density changing as the hyperbolic tangent, was obtained. Solution allows to restore all shock front and investigate its evolution for arbitrary values of the density change and position of the explosion point. The solution is applied for description of interaction of supernova remnants with molecular clouds.